FIQIH: DARI TRADISIONALISME, PEMBAHARUAN, HINGGA GEOPOLITIK - Marwah, Hasan Basri (UIN Sunan Kalijaga Yogyakarta, 2012)
One of the principal objects of cultural studies based on racial differentiation is Islam as a form of imaginative translation boundary that swept the Western world in general. Jurisprudence (Fiqh) is not just a question of legal manifestation and